Angular distributions in the decay B -> K*l(+)l(-) - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2009)
We use a sample of 384×106 BB̄ events collected with the BABAR detector at the PEP-II e+e- collider to study angular distributions in the rare decays B→K* + -, where + - is either e+e- or μ+μ-. For low dilepton invariant masses, m <2.5GeV/c2, we measure a lepton forward-backward asymmetry AFB=0.24-0.23+0.18±0.05 and K* longitudinal polarization FL=0.35±0.16±0.04. For m >3.2GeV/c2, we measure AFB=0.76-0.32+0.52±0.07 and FL=0.71-0.22+0.20±0.04. © 2009 The American Physical Society.